2010
DOI: 10.4049/jimmunol.0903253
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 Promotes B Cell Maturation: Independence and Cooperation with B Lymphocyte-Activating Factor

Abstract: We have previously shown that TLR4 triggering promotes the generation of CD23+CD93+ transitional T2-like cells in vitro from mouse B cell precursors, suggesting a possible role for this receptor in B cell maturation. In this study, we perform an extensive study of cell surface markers and functional properties of B cells matured in vitro with LPS, comparatively with the well-known B cell maturation factor B lymphocyte-activating factor (BAFF). LPS increased generation of CD23+ transitional B cells in a TLR4-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 49 publications
3
26
0
Order By: Relevance
“…Incubation of cells in the presence of BAFF for the last 18 h of culture in this system induces a 2-to 4-fold increase in the percentage and number of the CD23 + B cells compared with unstimulated control (Fig. 1A, 1C), in accordance with the well-known role of BAFF in B cell development at a transitional stage (13)(14)(15)28). Using BAFF as our comparative standard, we tested the effect of the incubation of B cells with IL-4 for the last 18 h of culture on developing B lymphocytes, analyzing changes in the expression of surface maturation markers by flow cytometry.…”
Section: Il-4 Stimulates In Vitro B Cell Maturationsupporting
confidence: 62%
See 2 more Smart Citations
“…Incubation of cells in the presence of BAFF for the last 18 h of culture in this system induces a 2-to 4-fold increase in the percentage and number of the CD23 + B cells compared with unstimulated control (Fig. 1A, 1C), in accordance with the well-known role of BAFF in B cell development at a transitional stage (13)(14)(15)28). Using BAFF as our comparative standard, we tested the effect of the incubation of B cells with IL-4 for the last 18 h of culture on developing B lymphocytes, analyzing changes in the expression of surface maturation markers by flow cytometry.…”
Section: Il-4 Stimulates In Vitro B Cell Maturationsupporting
confidence: 62%
“…In contrast to the relatively well-resolved roles of IL-4 in mature B cell activation, less clear is its role in B cell maturation and whether it can interfere on the pivotal roles of BCR/BAFF-R with a potential cooperation with BAFF in the control of autoreactivity at negative selection checkpoints. We have previously described that TLR4 agonists can affect B cell maturation in vitro by stimulating generation of T2-like B cells from BM developing B cells and cooperating with BAFF to enhance this process (27,28). These results suggested that TLR4 agonists can act as alternate/complementary factors for BAFF.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…24 Recent studies by Hayashi et al indicate that TLR4 signaling also plays a role during late stages of B-cell development by facilitating the generation of immature or transitional B cells. 14 The present study further demonstrates that early B-cell development is subject to regulation by TLR4 signaling. The pro-B-and pre-B-cell population was found to be enlarged in the bone marrow of TLR4-mutant, C3H/HeJ mice, indicating a physiological role of TLR4 in early B lymphopoiesis.…”
Section: Synergism Of Lps and Il-7 Signals In The Promotion Of Pre-bcmentioning
confidence: 70%
“…13 A more recent study, however, indicates that LPS may facilitate B-cell maturation by acting as an accessory stimulus to complement the BAFF physiological pathway of B-cell development. 14 Therefore, the precise role of TLR4 signaling in the early stages of B-cell development requires more in-depth analysis. In the present study, we used in vitro (cell culture) and in vivo (adoptive transfer) approaches to systemically analyze the impact of TLR4 signaling on the proliferation, survival and differentiation of B-cell precursors.…”
Section: Introductionmentioning
confidence: 99%